Pcb-3d-printed, reliable and reusable wells for impedance spectroscopy of aqueous solutions (2019)
Impedance Spectroscopy (IS) has been shown to be a non-invasive and reliable technique for the electrical characterization of biological materials. This paper presents the design and implementation of reliable, reusable wells that are used to perform IS measurements of aqueous solutions. These reusable wells are detachable, easy to clean and low-cost and they are made up of a platen on a Printed Circuit Board (PCB) and the chambers are manufactured using 3D-printing technology. In this case, in order to verify its functionality, IS measurements of electrolytic and non-electrolytic aqueous solutions were carried out. Initially, as a reference, the impedance spectrum of a Hanks’ solution was obtained following a proposed measurement protocol. Then, we analyse this spectrum and we propose an Equivalent Electrical Model (EEM) for validating the reusable wells. Finally, IS measurements are carried out on aqueous solutions of molecular D-glucose and sodium chloride prepared in Hanks’ solution and deionized water, by considering physiological concentrations. The parameter values of the EEMs of each solution tested were obtained using genetic algorithms and Matlab and, from these values, it is possible to conclude that the measurements performed are unable to differentiate the physiological concentration of glucose in the aqueous solution used. Also, from these results, it can be concluded that the designed wells are suitable for IS measurements of aqueous solutions and that they can be used in Electrical Cell Impedance Sensing (ECIS) or applications that require electrical characterization of solutions.